Acidic Electrolyzed Water as a Novel Transmitting Medium for High Hydrostatic Pressure Reduction of Bacterial Loads on Shelled Fresh Shrimp - Du, Suping; Zhang, Zhaohuan; Xiao, Lili; Lou, Yang; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2016)
Acidic electrolyzed water (AEW), a novel non-thermal sterilization technology, is widely used in the food industry. In this study, we firstly investigated the effect of AEW as a new pressure transmitting medium for high hydrostatic pressure (AEW-HHP) processing on microorganisms inactivation on shelled fresh shrimp. The optimal conditions of AEW-HHP for Vibrio parahaemolyticus inactivation on sterile shelled fresh shrimp were obtained using response surface methodology: NaCl concentration to electrolysis 1.5 g/L, treatment pressure 400 MPa, treatment time 10 min. Under the optimal conditions mentioned above, AEW dramatically enhanced the efficiency of HHP for inactivating V. parahaemolyticus and Listeria monocytogenes on artificially contaminated shelled fresh shrimp, and the log reductions were up to 6.08 and 5.71 log10 CFU/g respectively, while the common HHP could only inactivate the two pathogens up to 4.74 and 4.31 log10 CFU/g respectively. Meanwhile, scanning electron microscopy (SEM) showed the same phenomenon. For the naturally contaminated shelled fresh shrimp, AEW-HHP could also significantly reduce the micro flora when examined using plate count and PCR-DGGE. There were also no significant changes, histologically, in the muscle tissues of shrimps undergoing the AEW-HHP treatment. In summary, using AEW as a new transmitting medium for HHP processing is an innovative non thermal technology for improving the food safety of shrimp and other aquatic products.